Selected psychological factors related to pregnancy planning in women diagnosed with paranoid schizophrenia. Preliminary study - Studniczek, Anna; Łabęcka, Maryna; Kossakowska, Karolina (Kwartalnik Naukowy Fides et Ratio, 2022)
The presented research aimed to determine whether the selected psychological variables are related to the desire to have a child in childless women diagnosed with schizophrenia, to check the differences in terms of these variables between women diagnosed with schizophrenia who declare the will to have a child, and those who do not plan to have one, as well as the comparison of the results obtained in the group of women with no history of psychopathology. 30 women diagnosed with schizophrenia and 30 healthy women participated in the study. The Self-esteem Scale by Rosenberg and the Strength of character VIA-120 by Peterson and Seligman were used. The results indicate differences in self-esteem and selected character strengths between women who want to have a child and those who do not declare such a willingness and between the group of women diagnosed and the comparison group.